The Influence of Work Environment and Workload on Cyberloafing Behavior of Employees at Department of Education and Culture - Agus Siswanto; Zunan Setiawan; Roy Setiawan; Betty Rahayu; Musran Munizu (Departement of Mathematics Education, 2023)
This study's goal is to determine how the workplace environment, multiple roles, and workload affect their cyberloafing habits. In order to collect quantitative data for this study, questionnaires were distributed and library data were utilised. The data analysis technique used is multiple linear regression with SPSS 25. The data analysis methods used are coefficient of determination (R2), traditional assumption testing, hypothesis testing, and data quality testing. As shown by the significance level F < α (0.000 < 0 .05) and adjusted R square of 0.375, the findings of this study show that workload, multiple roles, and the work environment have an immediate and significant impact on cyberloafing behavior. Research indicates that 37.5% of cyberloafing behavior is caused by workload, multiple roles, and work environment.